KULTUR JARINGAN JERUK KASTURI (Citrus Microcarpa) DENGAN MENGGUNAKAN HORMON KINETIN DAN NAFTALEN ACETYL ACID (NAA) - Imam Mahadi; Wan Syafi’i; Suci Agustiani (DINAMIKA PERTANIAN, 2015)
Calamansi fruits is one horticulture crops to make juice and flavor foods. This research aimed to determine the effect of Kinetin and NAA on the growth of explants Musk lime (Citrus microcarpa). The results of this research showed of Kinetin and NAA significantly affect the growth of explants Musk Lime. The percentage of explants grown 100% all treatments, except treatment K5A0, The earliest of root rise in treatment K0A0,5 HST, The earliest of bud rise in treatment K5A0 HST, Highest amount of buds in treatment K3A2is 2.4 buds, Highest length of shoot in treatment K3A0is 7.1 buds, and the amount of roots the best treatment of K0A0,5is 8,1 roots.